60.5k views
3 votes
R+5/mn=p solve for m

1 Answer

5 votes

Answer:


\bold{m\ =\ \frac5{(p-r)n}}

Explanation:


\bold{r+\frac5{mn}\ =\ p}\\\\ {}\quad-r\qquad-r\\\\{}\ \ \bold{\frac5{mn}\ =\ p-r}\\\\{}\ ^(_*)(mn)\quad ^(_*)(mn)\\\\{}\quad\bold{5\ =\ (p-r)^(_*)(mn)}\\\\/(p-r)\quad/(p-r)\\\\{}\ \ \bold{\frac5{p-r}\ =\ mn}\\\\{}\quad \ / n\quad\ \ / n\\\\\bold{\frac5{(p-r)n}\ =\ m}

If you mean (r+5)/mn then:


\bold{(r+5)/(mn)\ =\ p}\\\\{}\ ^(_*)(mn)\quad ^(_*)(mn)\\\\{}\ \bold{r+5\ =\ pmn}\\\\/(pn)\quad/(pn)\\\\{}\ \ \bold{(r+5)/(pn)\ =\ m}

User Shanqn
by
5.1k points